Profitability of Citrus Tree Greenhouse Production Systems in Florida - Carlos Soils; Hayk Khachatryan; Richard Beeson (EDIS)
Nurseries are a vital part of the citrus industry in Florida, providing growers with trees for replanting and expanding citrus groves. As part of the response to citrus greening and canker disease in the industry, nursery-aimed regulations were set in place to try to guarantee the production of trees “free of virus or other graft transmittable diseases” in plant nurseries. The new regulations resulted in an important shift for producers from traditional open field groves to greenhouses. This 5-page fact sheet describes an experiment performed at the UF/IFAS Mid-Florida REC in Apopka to test the profitability of different inputs in citrus-producing greenhouse nurseries and provides recommendations that will be useful for the whole citrus-tree-producing sector. Written by Carlos Solis, Hayk Khachatryan, and Richard Beeson, and published by the Food and Resource Economics Department, October 2016.